Which is the best method of sterilization for recycled bone autograft in limb salvage surgery: a radiological, biomechanical and histopathological study in rabbit - Yasin, N.F.; Singh, Vivek Ajit; Saad, Marniza; Omar, E. (BioMed Central, 2015)
Background: Limb salvage surgery is a treatment of choice for sarcomas of the extremities. One of the options in skeletal reconstruction after tumour resection is by using a recycled bone autograft. The present accepted methods of recycling bone autografts include autoclaving, pasteurization and irradiation. At the moment there is lack of studies that compare the effectiveness of various sterilization methods used for recycling bone autografts and their effects in terms of bone incorporation. This study was performed to determine the effects of different methods of sterilization on bone autografts in rabbit by radiological, biomechanical and histopathological evaluations. Methods: Fresh rabbit cortical bone is harvested from the tibial diaphysis and sterilized extracorporeally by pasteurization (n = 6), autoclaving (n = 6), irradiation (n = 6) and normal saline as control group (n = 6). The cortical bones were immediately reimplanted after the sterilization process. The subsequent process of graft incorporation was examined over a period of 12 weeks by serial radiographs, biomechanical and histopathological evaluations. Statistical analysis (ANOVA) was performed on these results. Significance level (Α) and power (Β) were set to 0.05 and 0.90, respectively. Results: Radiographic analysis showed that irradiation group has higher score in bony union compared to other sterilization groups (p = 0.041). ANOVA analysis of 'failure stress', 'modulus' and 'strain to failure' demonstrated no significant differences (p = 0.389) between treated and untreated specimens under mechanical loading. In macroscopic histopathological analysis, the irradiated group has the highest percentage of bony union (91.7 percent). However in microscopic analysis of union, the pasteurization group has significantly higher score (p = 0.041) in callus formation, osteocytes percentage and bone marrow cellularity at the end of the study indicating good union potential. Conclusions: This experimental study shown that both irradiation and pasteurization techniques have more favourable outcome in terms of bony union based on radiographic and histopathological evaluations. Autoclaving has the worst outcome. These results indicate that extracorporeal irradiation or pasteurization of bone autografts, are viable option for recycling bone autografts. However, pasteurization has the best overall outcomes because of its osteocytes preservation and bone marrow cellularity.